Bioethanol production from empty fruit bunch (EFB) of oil palm - Zaini, Hajar Hadyan Hani (2006)
There are several methods to produce bioethanol. The bioethanol can be produced from cellulose and hemicelluloses that originate from many sources of biomass. The studies focused on the production of ethanol from oil palm waste using Saccaromyces cerevisie as fermentation aide to expand the usage of the oil palm waste. The purposes of this study were to determine the yield of ethanol produced from certain amount of biomass waste (oil palm wastes). Other than that the effects of different glucose concentration to the yield of bioethanol were studied. Besides, the effects of the different concentration of Saccaromyces cerevisae used to the yield of glucose production were studied too. Two sets of experiments were performed; in first set, the sample was hydrolyzed with pretreatment with sodium hydroxide then being subjected to sulfuric acid. The oil palm empty fruit bunch (EFB) is hydrolyzed using different concentrations of acid. Pretreatment is for break the lignin seal. At the second set the fermentation with Saccaromyces cerevisae was done in anaerobic condition. Different concentration of yeast was used in this experiment. The result showed that, the inoculums concentration did not have pronounced effect on the final ethanol concentration but the duration of fermentation decreased with the increase of the yeast concentration. It also showed that as the concentration of glucose increased, the ethanol concentration also increased where the highest final ethanol concentration with 15mg/ml of glucose was 13.8 % (w/w)